Modeling of transport infrastructure: ontological approach - K. Tkachenko; O. Tkachenko; O. Tkachenko (Збірник наукових праць Державного університету інфраструктури та технологій: серія "Транспортні системи і технології", 2023)
The article deals with current problems of ontological modeling of processes of design, construction and operation of buildings and structures in transport infrastructure. Such modeling involves use of standards and classifiers adopted in Europe and harmonized within BIM (Building Information Modeling) and EULYNX (European railway technology alliance). Multi-level ontological model of transport infrastructure is proposed. This model contributes to formation of understanding of essence of subject area, which is the field of transport infrastructure (transport repair enterprises, transport facilities (bridges, tunnels, tracks), transport depots, stations, etc.). Proposed model contributes to presentation of knowledge in form that is convenient for their processing in intelligent systems, ensuring intellectualization and digitization of processes in transport infrastructure. Proposed ontological approach ensures multiple use of knowledge and existing ontologies, allows the use of modern technologies (in particular, semantic ones), when objects of subject area correspond to their reflections in multi-level ontological model. Ontological approach to modeling of transport infrastructure makes it possible to move to automatic management of these objects and corresponding processes in systems that ensure intellectualization and digitalization of transport and transport infrastructure. Developed multi-level ontological model is planned to be supplemented with new components, imposing appropriate restrictions.